Analysis of flowering, fruitfulness, and production in two varieties of orange citrus sinensis l. oesbeck, and two varieties of tangerine citrus reticulata blanco, in palmira, the cauca valley (1992)
This work was made at the Instituto Colombiano Agropecuario, Palmira in the Cauca Valley. Twelve citric trees nine years old were used grafted with Cleopatra tangerine belonging to two oranges varieties: Nativa del  Chocó and Pera del Río and two tangerine varieties: Dancy and Wamurco. Flowering development was evaluated taking two trees per variety, epoch and intensity of flowering and fruitation, thicken percentage, fruit's development, fruits falled percentage. In addition, maduration and quality studies was made. Definite periods of highest flowering occurs in intervals of 15 to 30 days after intensity rainy day epoch. The thicken percentage of flowers and fruits, fruit's falled and fruit's development show differences among varieties and among trees of a single variety. The physiological maturity point measured by rate soluble solids/acidity, shows precocity of orange's varieties. About productive potential given by rate between fructifying and harvest are shown differences among varieties, fluctuantig between 9.2 and 44/6%.